Inequality in outpatient resource utilization among older adults during the 2007-2008 financial crisis: findings from Taiwan - Chiao-Lee Chu; Yu-Hua Chu; Chih-Yuan Lin; Yen-Ping Hsieh; Ching-Sung Ho; Yung-Yu Su; Chia-Nien Liu (BMC, 2019)
Abstract Background Equity in medical resource utilization is a crucial concern in countries with national health insurance systems. From the perspective of an active aging framework, public health insurance is one of the pillars of economic security, as suggested by the World Bank, to achieve the goal of social security for older adults. This study thus sought to quantify income-related inequality in national health insurance systems, especially during the global economic crisis of 2007-2008. Methods By employing the Taiwan National Health Interview Surveys (2005 and 2009) datasets, we analyzed the socioeconomic inequality of outpatient service utilization for older Taiwanese adults during the financial crisis of 2007-2008. We used corrected concentration indices (CCIs) to examine inequalities over time. Furthermore, we decomposed socioeconomic inequalities to reveal the contributions of determinant factors. The dependent variables related to whether participants had used outpatient services in the previous month, and the independent factors included individual's needs, enabling, predisposing, and environmental factors proposed by Andersen model. Results The sample consisted of 2415 observations in 2005 and 2554 observations in 2009. The income-related health care inequality was minor from pro-rich to pro-poor across the study duration, although the difference was insignificant (women: from a concentration index [CI] of 0.0256 in 2005 to a CI of − 0.0098 in 2009; men: from a CI of 0.0379 in 2005 to a CI of 0.0310 in 2009). We used a probit model to analyze the effect of explanatory factors on outpatient resource utilization by men and women. After other factors were controlled for, we found that that the income variable had a positive and significant effect on outpatient service utilization in 2009 and the absolute contribution of income to inequality notably increased from 0.0480 in 2005 to 0.3247 in 2009 for older women. Conclusions In conclusion, Taiwan's National Health Insurance system guarantees the accessibility of health care services to older adults, but slight income-related inequality was maintained in the outpatient resource utilization of women during the 2007-2008 financial crisis. Close attention should be paid to the vulnerability of women during times of economic insecurity.